Selective Amperometric Sensor for the Determination of Hydrazine at a Gold Nanoparticle Decorated Poly(Brilliant Blue) Modified Electrode - Dokur, Ebrar; Uruc, Selen; Suerkan, Sevdanur; Gorduk, Ozge; Sahin, Yucel (TAYLOR & FRANCIS INC, 2025)
There is a pressing requirement to synthesize stable electrode components that possess enhanced capabilities for creating electrochemical sensors, which are sensitive and discerning, to swiftly detect dangerous noxious substances. A sensitive electrochemical sensor has been developed in this study for hydrazine (HY) oxidation, utilizing gold nanoparticles (AuNPs) and poly(brilliant blue) (p(BB)) modifiers on the surface of the pencil graphite electrode (PGE). The features of the sensor for detecting hydrazine were characterized by electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), and X-ray photoelectron spectroscopy (XPS). Additionally, when examined under optimal parameters using CV and amperometry, the proposed hydrazine sensor presents favorable electrochemical and analytical figures of merit. The AuNPs/p(BB)/PGE provides the determination of low levels of hydrazine in water samples with a detection limit of 0.14 mu M. A wide linear range from 1.0 to 800 mu M was obtained. The findings indicate that the AuNPs/p(BB)/PGE sensor exhibits good stability, repeatability, and reproducibility for hydrazine. The proposed sensor was effectively used to determine hydrazine in both water and mineral water samples.
Keywords: Electrochemical analysis; gold nanoparticles (AuNPs); hydrazine; pencil graphite electrode (PGE); poly(brilliant blue); PENCIL GRAPHITE ELECTRODE; ELECTROCATALYTIC OXIDATION; ELECTROCHEMICAL SENSOR; CARBON NANOTUBES; CATECHOL; PALLADIUM; PASTE; Chemistry